ChemInform Abstract: Skeleton Transformation of α‐Pyrone Induced by 5‐Aryl Substituent into Ring‐Fused Dihydrofuran. Issue 31 (5th August 2014) - Miura, Takuya; Fujioka, Saki; Iwasaki, Hiroki; Ozeki, Minoru; Kojima, Naoto; Yamashita, Masayuki
Abstract Dimethylsulfoxonium methylide (II) is prepared in situ from trimethylsulfoxonium iodide and sodium hydride.